2018
DOI: 10.1016/j.clinimag.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Second opinion interpretation of breast ultrasound images-Is it worth another look?

Abstract: RTUR was found to be an important tool in the management of patients at our comprehensive cancer center. Although additional false-positive lesions may be detected on RTUR, a great number of patients will benefit from RTUR in finding additional cancers or avoiding unnecessary biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
3
4
1
Order By: Relevance
“…The 27% discrepancy frequency in our study is similar to that for previous studies of second opinion breast imaging review which ranges from 18 to 57% [ 1 8 , 10 ]. A previous study focusing specifically on MRI discrepancy frequency demonstrated a lower frequency (18%) than breast imaging review overall.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The 27% discrepancy frequency in our study is similar to that for previous studies of second opinion breast imaging review which ranges from 18 to 57% [ 1 8 , 10 ]. A previous study focusing specifically on MRI discrepancy frequency demonstrated a lower frequency (18%) than breast imaging review overall.…”
Section: Discussionsupporting
confidence: 89%
“…In their study, 33% of patients with second-look ultrasound resulting from discrepant review resulted in additional biopsies being performed or averted, which is similar to the 35% observed in our study. They also demonstrated a PPV3 of 25% for the added biopsies, slightly lower than the PPV3 of 36% in the breast and 31% in the axilla demonstrated in our study [ 10 ].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…These screenshots are static and isolated, which may lead to uncertain or unobjective assessment in characterizing the BI-RADS stage of lesions. 4 An SOUS is low cost and may benefit the majority of these patients if predictive factors that correlate with malignancy and benignancy can be identified. An SOUS is defined as re-evaluation of a lesion(s) via ultrasound within 2 weeks, with total independence from the first examination and evaluation by a different radiologist.…”
Section: Introductionmentioning
confidence: 99%